Analisis Komparasi Kinerja Keuangan Perusahaan Farmasi Bumn Dengan Bums Yang Terdaftar Di BEI Tahun 2020-2022 - Fikron Achmad Al-Fansuri; Rendra Arief Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research was conducted to find the results of differences in financial performance through profitability, liquidity, solvency and activity ratios in state-owned and private pharmaceutical companies in 2020-2022, where the novelty phenomenon is the phenomenon from the time of Covid-19 to after Covid-19. Because researchers see the problem of state-owned pharmaceuticals experiencing losses while private companies experience profits with the same company size. The research used independent sample t-test and Mann Whitney U statistical tests which obtained superior BUMS pharmaceutical results compared to BUMN. The loss factors found in BUMN were losses in sales of vaccines, medical devices and vitamins in 2021-2022, this was caused by BUMN's negligence in managing production volumes and indirectly due to regulations from the Minister of Health and the President regarding the Covid-19 emergency response. The benefits that can be taken by various parties are investment considerations and consideration of the suitability of utilization and production management so that it meets expectations.